Increasing Ca2+ accumulation in salt glands under salt stress increases stronger selective secretion of Na+ in Plumbago auriculata tetraploids - Duan, Yifan; Jiang, Liqiong; Lei, Ting; Ouyang, Keyu; Liu, Cailei; Zhao, Zi’an; Li, Yirui; Yang, Lijuan; Li, Jiani; Yi, Shouli; Gao, Suping (Frontiers in Plant Science, 2024)
Under salt stress, recretohalophyte Plumbago auriculata tetraploids enhance salt tolerance by increasing selective secretion of Na + compared with that in diploids, although the mechanism is unclear. In this study, salt gland Ca 2+ content and its effects on Na + and K + secretion were investigated in diploid and tetraploid P. auriculata under salt stress. Salt gland Ca 2+ accumulation and Na + and K + secretion rates were higher in tetraploids than in diploids under salt stress. Calcium addition increased Ca 2+ content in diploid but not in tetraploid salt glands. Diploid salt glands also increased Na + and K + secretion rates with Ca 2+ addition, decreasing differences with those of tetraploids. With addition of a Ca 2+ channel inhibitor, diploid salt glands retained large amounts of Ca 2+ , leading to higher Ca 2+ content and Na + secretion rate than those of tetraploids. Inhibiting H2O2 generation and H + -ATPase activity altered Na + and K + secretion rates in diploids and tetraploids under salt stress, indicating involvement in regulating Na + and K + secretion. Inhibition also suppressed tetraploid but increased diploid K + secretion rate, suggesting membrane depolarization-activated K + efflux channels affected salt gland K + secretion, with greater effects in diploids than in tetraploids. Therefore, increased salt gland Na + secretion rate in tetraploids under salt stress was associated with elevated salt gland Ca 2+ . The Ca 2+ may regulate Na + and K + secretion by modulating H2O2 generation or H + -ATPase activity, whereas depolarization-activated K + efflux channels may affect salt gland K + secretion.